Over a million students use our free study notes to help them with their homework
3x + 6 > 3 - 2x. Firstly move the numerical terms to one side. 3x + 3 > - 2x. Secondly, move all x terms to the same side. 5x + 3 > 0. Finally, put the numerical and x terms to opposite sides, an...
When you are expanding a double bracket you have to multiply each each in one bracket against the two others terms in the other bracket. So starting with X: X times the first term in the other bracket whi...
First rearrange the equation dy/dx = x3 + 5x Then move the dx to the RHS of the equation dy = ( x3+ 5x)dxThen integrate both sides, with respect to y on the LHS and with respect to x...
This is a simple differentiation example of a polynomial, where one uses the the standard algorithm - i.e.[nx^n-1] Ina polynomial, one differentiates all parts separately. First Take 3x^2. Multiply by the...
We can find dy/dx by using the product rule: If y=uv then dy/dx = u (dv/dx)+ v (du/dx). In this question u= sin(6x) and v= sec(2x).So du/dx= 6cos(6x) and dv/dx=2sec(2x)tan(2x), using our rules for differe...
←
681
682
683
684
685
→
Internet Safety
Payment Security
Cyber
Essentials